Bilateral staghorn lithiasis: a case report - Orozco, Cesar Alberto Ortiz; Gutiérrez, Felix Osuna; Torres, José María Zepeda; Fernandez, Carlos Navarro; Solís, Pablo Francisco Rojas; Ayala, José Miguel Aceves; Casas, Ashley Yael Sotelo (International Surgery Journal, 2022)
Staghorn stones are large branching stones that fill part of the entire renal pelvis and calyces and can be complete or partial depending on the degree of occupation of the collecting system. Although kidney stones are more common in men, coral stones are reported less frequently in men than in women and are usually unilateral. Due to the significant morbidity and potential mortality attributed to staghorn stones, prompt evaluation and treatment are imperative. In general, the gold standard treatment for coral stones is surgical treatment to achieve a stone-free collecting system and preserve renal function.